Roman theatres : an architectural study - Sear, Frank (Oxford University Press, 2006)
This book is an up-to-date and comprehensive account of Roman theatre architecture. It contains information, plans, and photographs of every theatre in the Roman Empire for which there is archaeological evidence, together with a full analysis of how Roman theatres were designed, built, and paid for, and how theatres differ in different parts of the Roman Empire. It is lavishly illustrated with plans, text figures, photographs, and maps. - ;This book is a definitive architectural study of Roman theatre architecture. In nine chapters it brings together a massive amount of archaeological, literar.
Keywords: Theaters -- Rome.; Archaeology -- Rome.; Rome -- Antiquities -- Catalogs.; Archéologie -- Rome.; Rome -- Antiquités -- Catalogues.; ARCHITECTURE -- Buildings -- Public, Commercial & Industrial.; Antiquities; Archaeology; Theaters; Rome (Empire); Catalogs